The impact of Digital technology on the transformation of political culture of modern Kazakhstani youth (Journal of history, 2021)
In the article authors examines the reasons for the transformation of political culture and consciousness of young people on the way to the formation of civil society in the modern period. Among several existing factors of transformation, the authors study the active introduction of modern digital technologies into the social and political life of society. Beside this process, the article analyzes the growing influence of digital technology on the political consciousness of Kazakhstani youth. Authors argue which digital technologies have become the main tool in shaping the political views and attitudes of young people in the process of political socialization of modern youth. In order to prove the hypothesis author analyzed the influence of the virtual space on the growth of politi cal activity of Kazakhstani youth by using latest statistical data from official resources. Based on the experience of digitalized society authors make a forecast on the challenges and threats posed by modern digital technologies for young people and their political behavior. On the way to reveal and identify problems with digitalization, the authors used the method of comparative analysis, as well as historical and sociological methods.Key words: political culture, Kazakhstani youth, modern digital technologies, internet, digital culture, digitalization.